Securitization on the Spread of COVID-19 in Indonesia [Sekuritasasi dalam Penyebaran Covid-19 di Indonesia] - Cornelia Clara Tifany (Jurnal Politica, 2020)
Based on the World Health Organization report, Coronavirus disease 2019 (COVID-19) is an infectious respiratory disease that has become an epidemic in approximately 213 countries throughout the world, including Indonesia. Prior to the first confirmed case of COVID-19 in Indonesia, the Indonesian government’s response, as represented by its high-level officials, suggested a lack of awareness. Some situations then became the turning points for the Indonesian Government, who has since focused more on dealing with the COVID-19 outbreak. Through this research, the writer aims to analyze the Indonesian Government’s treatment of COVID-19 from a health issue to a security issue. Therefore, the securitization theory focusing on the component of securitization from Buzan will be employed as an analytical framework in this research. In addition, the global health governance is also used as a reference to support the writer’s statement. In order to explain the action of the Indonesian Government, this research will use qualitative research with a focus on literacy observations through online news relating to the issues. In conclusion, the change in action of the Indonesian Government was caused by the pressure from GHG, which then showed that the spread of COVID-19 in Indonesia is a security issue.AbstrakCoronavirus disease (COVID-19) yang merupakan penyakit pernapasan menular telah mewabah kurang lebih di 213 negara di dunia berdasarkan pada laporan World Health Organization, salah satu negara yang terkena wabah adalah Indonesia. Sebelum ada konfirmasi atas kasus COVID-19 di Indonesia, terlihat sikap pihak pemerintah yang diwakili oleh pejabat tinggi menunjukkan sikap kurang perhatian. Namun beberapa situasi menjadi “turning point” bagi Pemerintah Indonesia yang kemudian memberikan fokus yang lebih dalam menghadapi wabah COVID-19 di Indonesia. Dari keadaan tersebut melalui penelitian ini, penulis menganalisis sikap Pemerintah Indonesia dalam mengubah isu kesehatan menjadi isu keamanan. Penelitian ini menggunakan teori sekuritisasi sebagai kerangka analisis dengan terfokus pada komponen sekuritisasi oleh Buzan. Di samping itu juga menggunakan tata kelola kesehatan global sebagai penopang pernyataan penulis. Agar mampu menjelaskan sikap Pemerintah Indonesia maka penelitian ini menggunakan metode penelitian kualitatif dengan fokus pada pengamatan literasi melalui berita daring yang berkaitan dengan permasalahan yang diangkat. Dalam kesimpulannya, perubahan sikap Pemerintah Indonesia disebabkan oleh adanya tekanan dari tata kelola kesehatan global yang menunjukkan bahwa penyebaran COVID-19 di Indonesia merupakan isu keamanan.